2004
DOI: 10.1111/j.1463-1326.2004.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between cord blood adiponectin concentrations and the number of cigarettes smoked during pregnancy

Abstract: Our findings also reveal a significant relationship between the reported number of cigarettes smoked during pregnancy and cord blood adiponectin concentrations (p = 0.01), suggesting that this association could have a causal relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15). The current study found a positive correlation between adiponectin concentration and gestational age in the GDM group although there was no such correlation in the NGT group.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15). The current study found a positive correlation between adiponectin concentration and gestational age in the GDM group although there was no such correlation in the NGT group.…”
Section: Discussioncontrasting
confidence: 39%
“…In adults, adiponectin concentration is inversely related to adiposity, but its association with adiposity is poorly understood (9,11,13). Some studies indicate a positive correlation between cord plasma adiponectin concentration and adiposity in infants (8,12,14,(16)(17)(18)(19)(20) and some have found no significant correlation (9,15).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
“…Most prior studies found no difference in cord blood leptin [12, 14, 15, 21] or adiponectin [14] in infants of mothers who smoked versus did not smoke during pregnancy, although a few found lower cord blood leptin [18] and adiponectin [12, 20] in infants of smokers. While prior studies did not evaluate the association between prenatal smoking and C-peptide, thought to be a more stable marker of pancreatic function than insulin due to its longer half-life [38], of two studies that evaluated cord blood insulin, one [19] found lower insulin in smokers, and the other [14] found no difference in smokers versus non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, cord blood adiponectin was lower in pregnancies of mothers who smoked compared to nonsmokers [29] . This observation could be of relevance for our findings, because maternal smoking is negatively associated with risk of preeclampsia [30] .…”
Section: Discussionmentioning
confidence: 99%